A systematic review of sacral nerve stimulation mechanisms in the treatment of fecal incontinence and constipation. Issue 9 (September 2014) - Carrington, E. V.; Evers, J.; Grossi, U.; Dinning, P. G.; Scott, S. M.; O'Connell, P. R.; Jones, J. F. X.; Knowles, C. H.
Abstract Background Sacral nerve stimulation (SNS) is now well established as a treatment for fecal incontinence (FI) resistant to conservative measures and may also have utility in the management of chronic constipation; however, mechanism of action is not fully understood. End organ effects of SNS have been studied in both clinical and experimental settings, but interpretation is difficult due to the multitude of techniques used and heterogeneity of reported findings. The aim of this study was to systematically review available evidence on the mechanisms of SNS in the treatment of FI and constipation. Methods Two systematic reviews of the literature (performed in accordance with the Preferred Reporting Items for Systematic reviews and Meta‐Analyses framework) were performed to identify manuscripts pertaining to (a) clinical and (b) physiological effects of SNS during the management of hindgut dysfunction. Key Results The clinical literature search revealed 161 articles, of which 53 were deemed suitable for analysis. The experimental literature search revealed 43 articles, of which nine were deemed suitable for analysis. These studies reported results of investigative techniques examining changes in cortical, gastrointestinal, colonic, rectal, and anal function. Conclusions & Inferences The initial hypothesis that the mechanism of SNS was primarily peripheral motor neurostimulation is not supported by the majority of recent studies. Due to the large body of evidence demonstrating effects outside of the anorectum, it appears likely that the influence of SNS on anorectal function occurs at a pelvic afferent or central level.